Antigenic relatedness between the spiralins of Spiroplasma citri and Spiroplasma melliferum. - Zaaria, A (1990)
Four spiralins were compared by rocket immunoelectrophoresis, quantitative immunoblotting techniques, and the spiroplasma deformation test with the use of antispiralin (polyclonal) monospecific antibodies. This investigation revealed that the spiralins of Spiroplasma citri and S. melliferum are antigenically related and that probably no more than two epitopes simultaneously saturable with antibodies are shared by the two proteins. One at least of these epitopes is accessible to antibodies on the spiroplasma cell surface.